Stereotypical versus experiential destination branding: The case of Milan city. (June 2019) - De Noni, Ivan; Orsi, Luigi; Zanderighi, Luca
Abstract: In the last decades several contributes have tried to provide theoretical solutions and models for measuring the value of a place, a destination, a city. Specifically, some of them have explored the role several factors and different stakeholders play in the place branding evaluation and perception process. However, no conclusive findings are documented and several aspects need to be further investigated. In order to extend the understanding of city branding, this study focuses on the perceived image of Milan and performs a gap analysis by exploring specific factors and specific types of stakeholders. Based on target's provenance and degree of knowledge of city, stereotypical and experiential perceptions of Milan are measured with respect to nine main city attributes as summarized by literature background and compared to the brand values of some important European cities. The findings highlight a mismatch between the stereotypical and experiential perception at different levels and provide the framework to inspire more effective marketing policies for the improvement of city's image. Highlights: This study focuses on the perceived image of Milan and performs a gap analysis. Stereotypical and experiential perceptions of the city of Milan are measured. The findings highlight a mismatch between the stereotypical and experiential perception at different levels.